Hemorrhagic Disease of The Newborn - Ratih Nawang Wulan (LPPM UIN Sulthan Thaha Saifuddin Jambi, 2022)
The incidence of HDN in infants who do not receive prophylactic vitamin K in various countries is reported to vary. Researchers implement Midwifery Care for Neonates with Hemorrarchic Diseases of the Newborn (HDN) using the midwifery management mindset according to Varney and documenting care in the form of SOAP. The study used an observation method on a 4-day-old baby with a history of premature birth at 34-45 weeks of gestation and was born by Sectio Caesarea with indications of Placenta Previa Totalis. HDN in this case was classified as classic HDN because it occurred 4 days after birth and was followed by several symptoms such as bleeding from the digestive system and followed by prolonged PPT without any thrombocytopenia or other abnormalities on physical examination.